2021
DOI: 10.1111/tpj.15187
|View full text |Cite
|
Sign up to set email alerts
|

A conservative pathway for coordination of cell wall biosynthesis and cell cycle progression in plants

Abstract: The mechanism that coordinates cell growth and cell cycle progression remains poorly understood; in particular, whether the cell cycle and cell wall biosynthesis are coordinated remains unclear. Recently, cell wall biosynthesis and cell cycle progression were reported to respond to wounding. Nonetheless, no genes are reported to synchronize the biosynthesis of the cell wall and the cell cycle. Here, we report that wounding induces the expression of genes associated with cell wall biosynthesis and the cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 64 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…We observed that the repression of both PKS4 and PKS2 by wounding under sun-mimicking conditions was not visible in the aos mutant ( S8 Fig ). This result is consistent with previous reports showing a down-regulation of PKS2 and PKS4 upon wounding [ 44 ] or MeJA treatment [ 45 , 46 ] in green seedlings or leaves. We thus conclude that the impact of wounding on PKS expression depends on the jasmonate pathway.…”
Section: Resultssupporting
confidence: 94%
“…We observed that the repression of both PKS4 and PKS2 by wounding under sun-mimicking conditions was not visible in the aos mutant ( S8 Fig ). This result is consistent with previous reports showing a down-regulation of PKS2 and PKS4 upon wounding [ 44 ] or MeJA treatment [ 45 , 46 ] in green seedlings or leaves. We thus conclude that the impact of wounding on PKS expression depends on the jasmonate pathway.…”
Section: Resultssupporting
confidence: 94%
“…Several plant MYB TFs, in particular of R1R2R3-type, have been shown to regulate cell cycle [ 74 ], and this function has been reported also for the AtMYB59, AtMYB125, FOUR LIPS/AtMYB124, AtMYB88, AtMYB46, and AtMYB83 R2R3-type MYBs [ 74 , 75 , 76 , 77 , 78 ]. For AtMYB4 and its orthologues involvement in the control of cell cycle has not been reported; however, the reduced plant stature in different species overexpressing MYB4 orthologues, the faster growth rate of the AtMYB4oe cardoon lines, and the differences in their transcriptional modulation of cell cycle genes as compared with WT suggest a possible role of AtMYB4 in the regulation of cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, it was very recently shown that AtMYB46 and AtMYB83 in Arabidopsis thaliana and RrMYB18 in Rosa rugosa are induced by wounding, and regulate the expression of genes involved in cell wall biosynthesis, including lignin, and cell cycle progression. Moreover, expression correlation analysis in different species revealed that this co-regulation of genes involved in both processes is highly conserved [ 74 ]. These results question the previous accepted suggestion that these two processes are independently regulated [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the transcription factor MYB46 in A. thaliana has emerged as a key player, orchestrating cell growth and cell cycle progression. MYB46 expression is induced upon wounding, leading to the upregulation of genes associated with cell wall biosynthesis and the cell cycle (Shi et al 2021 ). This coordinated response promotes the biosynthesis of the cell wall by enhancing the expression of cell wall-associated genes.…”
Section: Current Understanding Of Cell Wall Integrity and Cell Cycle ...mentioning
confidence: 99%
“…This coordinated response promotes the biosynthesis of the cell wall by enhancing the expression of cell wall-associated genes. Also, it upregulates a battery of genes involved in cell cycle progression (Shi et al 2021 ). The involvement of MYB46 in this regulatory network has been observed in seven plant species harboring R2R3-MYB domains, including A. thaliana , Fragaria vesca (strawberry), Malus domestica (apple), Prunus mume (plum blossom), Prunus persica (peach), Pyrus bretschneideri (pear), and Rosa chinensis (China rose), highlighting its evolutionary conservation (Shi et al 2021 ).…”
Section: Current Understanding Of Cell Wall Integrity and Cell Cycle ...mentioning
confidence: 99%